Southeast Asian education in modern history
1 online resource.
Keywords: "Social, political and economic change in Southeast Asia of the last two hundred years has been faster and more substantial than in any previous age as the impact of the Industrial Revolution intruded into the region and, particularly over the last fifty years, manifested itself in patent and tangible measures of the region's productivity reflecting unprecedented sustained economic growth. This book analyses the Southeast Asian experience of educational development. Through a variety of micro-historical studies on the subject of education, policy and practice in the region from the emergence of modern education to the end of the twentieth century, the book examines if there is an identifiably distinct Southeast Asian approach to the provision of education. Contributors focus on issues connected to schools and modernity, schools and politics, schools and the actions of Western teachers in the region. They also explore the extent to which contest over educational content in schools has occurred and establish the particular socio-cultural, political and economic bases upon which these contestations have played out. Demonstrating that education has been facilitated by the region's particular configurations, its unique demographic, religious, social, environmental, economic and political context, the book presents the obstacles that have prevented education making as full an impact on the region's rate of change. An analysis of the history of schools in Southeast Asia, this book offers a valuable explanation of the current state of education in Southeast Asia and the challenges it has inherited. This book will be of interest to academics in the field of Southeast Asian Studies, Asian Studies, education, nationalism, and history" --